Influence of Nonaxisymmetric Flow Injection into the Diffuser on the Turbine LPC Exhaust Nozzle - Subotovich, Valery; Yudin, Yuriy; Lapuzin, Alexander; Yudin, Alexander; Shvetsov, Victor (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
The data of computational aerodynamic investigations carried out for the diffuser used by the discharge nozzles of modern steam turbines have been given. The calculations were done using the axisymmetric statement for the three options of flow turn to the collection chamber of exhaust nozzles. During the computation, we varied the parameters of special flow injection at the external diffuser by-pass and took into account the above-shroud leakage. The following characteristics were analyzed, in particular the flow injection jet pulse coefficient and the coefficients of net, internal and outlet velocity losses of the diffuser. It was shown that the outlet velocity loss produced the basic influence on the level of net losses of the diffuser due to the flow pattern and the availability of separated circulation zones, and the diffuser flow and the flow of nonaxisymmetric collection chamber of the exhaust nozzle are subjected to the substantial influence of flow injection parameters. Optimal parameters of the injection jet were determined taking into consideration the flow discharge from the exhaust nozzle into the capacitor of a cellar type. The recommendations were given on how to improve the aerodynamic characteristics of the diffuser due to a change in the structure in the region of special injection of the flow. A circumferential change in the size of the output slit of circular channel at the invariable total area of steam output allows for a decrease of mixing losses in the collection chamber and circular nonuniformity of the pressure behind the last cascade for the diffuser cowling flow without separation that results in a decrease of the net losses of exhaust nozzle. Proposed recommendations can be used to provide special injection of the flow of wet steam mixture removed from the circumferential zone of the last stage, increasing thus the efficiency of the exhaust zone of steam turbine with the cellar arrangement of the capacitor and retaining the erosion reliability of the last stage of low pressure cylinder.